Biofilm and Planktonic Antibiotic Resistance in Patients With Acute Exacerbation of Chronic Rhinosinusitis - Sabino, Henrique Augusto Cantareira; Valera, Fabiana Cardoso Pereira; Santos, Denise Vieira; Fantucci, Marina Zilio; Titoneli, Carolina Carneiro; Martinez, Roberto; Anselmo-Lima, Wilma T.; Tamashiro, Edwin (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction The recalcitrant nature of patients with acute exacerbation of chronic rhinosinusitis (AECRS) potentially involves persisting colonization of the sinonasal mucosa by bacterial biofilms. Biofilms are known to be highly resistant to antibiotics, which may trigger or maintain chronic inflammation in the sinonasal mucosa. However, little is known about the relationship between the minimum inhibitory concentration (MIC) and antibiofilm concentrations of bacteria obtained from AECRS patients. Material and Methods Thirty bacterial strains from 25 patients with AECRS were identified and underwent MIC determination (VITEK® 2). The planktonic isolates were submitted to an in vitro formation of biofilms (Modified Calgary Biofilm Device) and determination of minimum biofilm inhibitory concentration (MBIC) and minimum biofilm eradication concentration (MBEC) for amoxicillin, amoxicillin/clavulanic acid, clarithromycin, and levofloxacin. MIC of the planktonic forms was compared with MBIC and MBEC levels, according to the breakpoints established by the Clinical Laboratory Standards Institute guidelines. Results The main bacteria retrieved was S. aureus (60%), followed by other Gram-positive and Gram-negative bacteria in lower frequencies. 76.7% of strains formed biofilm in vitro (n=23/30). The planktonic isolates presented high rates of resistance for amoxicillin (82.6%) and clarithromycin (39.1%), and lower rates for amoxicillin/clavulanic acid (17.4%). The biofilm-forming bacteria counterparts presented higher levels of MBIC and MBEC compared to the MIC levels for amoxicillin, amoxicillin/clavulanic acid, and clarithromycin. Levofloxacin was highly effective against both planktonic and biofilm forms. Planktonic resistant forms were associated higher levels of antibiofilm concentrations (MBIC and MBEC). Conclusions Biofilm-forming bacteria from AECRS patients are prevalent, and biofilm forms are highly resistant to antibiotics compared to their planktonic counterparts. Antibiotic resistance observed in planktonic forms is a good indicator of biofilm resistance, although near 20% of susceptible planktonic bacteria can produce antibiotic tolerant biofilms.